The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1ra08261b
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic turnover of CO2 under visible light by [Re(CO)3(1-(1,10) phenanthroline-5-(4-nitro-naphthalimide))Cl] in tandem with the sacrificial donor BIH

Abstract: Rhenium based photocatalytic conversion CO2 to formate in the visible region with excellent turnover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This temperature dependence suggests that this latter emissive band is associated with a 3 MLCT transition, as previously observed for similar Re complexes. 54 Computational studies revealed that upon the introduction of spin-orbit coupling (SOC) via the spin-orbit mean field (SOMF) 55 approach the character of the second band becomes more convoluted. Scalar roots S8 and S9 are quasi-degenerate and exhibit oscillator strength values of 0.128 and 0.342, respectively.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…This temperature dependence suggests that this latter emissive band is associated with a 3 MLCT transition, as previously observed for similar Re complexes. 54 Computational studies revealed that upon the introduction of spin-orbit coupling (SOC) via the spin-orbit mean field (SOMF) 55 approach the character of the second band becomes more convoluted. Scalar roots S8 and S9 are quasi-degenerate and exhibit oscillator strength values of 0.128 and 0.342, respectively.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Transition-metal complexes as a kind of molecular catalysts for homogeneous systems have attracted enormous attention due to their clear molecular structures and catalytic active sites, which facilitates the exploration of the relationship between structure and catalytic performance . In recent years, various precious metal (such as Re, Ir, Au, , and Ru , ) complexes have been employed as molecular catalysts for photocatalytic reduction of CO 2 . Although these kind of complexes usually display excellent photocatalytic performance for CO 2 reduction, the development of nonprecious metal (such as Co, Mn, Ni, , and Fe ) complex catalysts has become a hot spot due to the high cost of precious metal complexes.…”
Section: Introductionmentioning
confidence: 99%